Core–Shell‐Heterostructured Magnetic–Plasmonic Nanoassemblies with Highly Retained Magnetic–Plasmonic Activities for Ultrasensitive Bioanalysis in Complex Matrix. Issue 2 (13th December 2019) - Hao, Liangwen; Leng, Yuankui; Zeng, Lifeng; Chen, Xirui; Chen, Jing; Duan, Hong; Huang, Xiaolin; Xiong, Yonghua; Chen, Xiaoyuan
Abstract: Herein, a facile self‐assembly strategy for coassembling oleic acid‐coated iron oxide nanoparticles (OC‐IONPs) with oleylamine‐coated gold nanoparticles (OA‐AuNPs) to form colloidal magnetic–plasmonic nanoassemblies (MPNAs) is reported. The resultant MPNAs exhibit a typical core–shell heterostructure comprising aggregated OA‐AuNPs as a plasmonic core surrounded by an assembled magnetic shell of OC‐IONPs. Owing to the high loading of OA‐AuNPs and reasonable spatial distribution of OC‐IONPs, the resultant MPNAs exhibit highly retained magnetic–plasmonic activities simultaneously. Using the intrinsic dual functionality of MPNAs as a magnetic separator and a plasmonic signal transducer, it is demonstrated that the assembled MPNAs can achieve the simultaneous magnetic manipulation and optical detection on the lateral flow immunoassay platform after surface functionalization with recognition molecules. In conclusion, the core–shell‐heterostructured MPNAs can serve as a nanoanalytical platform for the separation and concentration of target compounds from complex biological samples using magnetic properties and simultaneous optical sensing using plasmonic properties. Abstract : Herein, the facile synthesis of magnetic–plasmonic nanoassemblies (MPNAs) is reported, which exhibit a typical core–shell structure, wherein oleylamine‐coated gold nanoparticles (OA‐AuNPs) preferentially aggregate and form a plasmonic core and oleic acid‐coated iron oxide nanoparticles (OC‐IONPs) assemble a magnetic shell. The resultant MPNAs hold the highly retained magnetic–plasmonic activities for the separation and simultaneous optical sensing of target compounds in complex biological samples.